Analisis Perencanaan Rute Distribusi Beras Premium Menggunakan Metode Vehicle Routing Problem Dengan Algoritma Tabu Search - Azizi, Dimas Akbar; Sholihah, Sita Aniisah; Sitorus, Purbanuara Parlindungan (Jurnal Sistem Transportasi & Logistik, 2025)
PT. X focuses on warehousing logistics, transportation, and pest eradication services. In the distribution of rice, PT. X hands over to its subsidiary engaged in transportation services. The subsidiary of PT. X has problems faced, namely the number of varied delivery destinations, different requests for each customer and route determination still relying on the experience of the driver. Therefore, this research was conducted to determine the optimal route in delivery, by minimizing the total distance traveled, calculating the total minimum cost resulting from the calculation of the Tabu Search Algorithm. The results of the study, the total distance on the company's initial 4 routes amounted to 372.6 Km and the overall initial cost of 4 routes incurred by the company amounted to Rp. 1,654,244. After using the Tabu Search Algorithm, 3 new route proposals were generated amounting to 298.5 Km and the overall cost for 3 routes was Rp. 1,339,223 which means getting a distance savings of 74.1 Km and shipping cost savings of Rp. 315,021. The route results obtained using the Tabu Search Algorithm are, Route 1: (0-C4-C60) with a distance of 45.8 Km, route 2: (0-C1-0) with a distance of 85 Km, route 3: (0-C3-C5-C2-0) with a total distance of 167.7 Km.